Antirust soft magnetic composite material and preparation method and application thereof
Through multi-step coating technology, nano-oxides and silane coupling agents are used to form a stable coating layer, which solves the problem that iron-based alloy soft magnetic composite materials are prone to rust when the air is humid or left aside for a long time, achieving long-term and comprehensive Anti-rust while maintaining the material's magnetic properties.
Patent Information
- Application Number
- CN202411919451.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-12-24
AI Technical Summary
Existing iron-based alloy soft magnetic composite materials are prone to rust when the air is wet or shelved for a long time, and have poor corrosion resistance. Common anti-rust methods such as spray paint, anti-rust oil or silane coupling agent are costly and have high pollution. , deterioration of magnetic properties and other problems.
Using multi-step coating technology, the iron-based powder is first coated and annealed with a coating liquid, and then the second coating is performed, using nano-oxide and silane coupling agent to form a stable coating layer to enhance rust prevention performance.
It achieves long-term and comprehensive rust prevention of iron-based alloy soft magnetic composite materials, avoids corrosion problems, maintains the magnetic properties of the material, and reduces the loss of products.
Smart Images

Figure CN119361316A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of soft magnetic materials, and in particular relates to a rust-proof soft magnetic composite material and a preparation method and application thereof. Background Art
[0002] Common iron-based alloy soft magnetic composite materials include iron-silicon soft magnetic composite materials, iron-silicon-aluminum soft magnetic composite materials, iron-nickel soft magnetic composite materials and pure iron soft magnetic composite materials, which are widely used in power electronic equipment such as active filters, inverters, and uninterruptible power supplies. At present, soft magnetic composite materials are mostly prepared by powder metallurgy processes such as insulation coating, pressing and annealing heat treatment, and have the advantages of easy processing and excellent magnetic properties. However, since most soft magnetic composite materials are composed of iron as the main component, they are prone to rust in humid air or long-term storage, and their corrosion resistance is poor. In order to prevent the iron-based alloy soft magnetic composite materials from rusting, spraying paint or soaking in anti-rust oil is often used in actual production to isolate the magnetic core from the air to prevent rust. However, spraying paint is easy to pollute the environment, and the outer skin of the paint layer is prone to fall off after long-term use; while soaking the magnetic core with anti-rust oil, since the air in the tiny air gap inside the magnetic core is difficult to be completely discharged, it is difficult for the anti-rust oil to completely enter the air gap inside the magnetic core, and it is difficult to achieve the purpose of comprehensive and long-term rust prevention. In addition, some researchers use silane coupling agents to prevent rust on soft magnetic composite materials. However, this method requires acid or alkali washing of the magnetic core during the rust prevention process. Strong acids and strong bases are generally used. Both strong acids and strong bases will passivate the surface of the magnetic powder, thereby causing the deterioration of the magnetic properties of the soft magnetic composite materials. Therefore, developing a process method that does not affect the magnetic properties of the magnetic core and can achieve long-term and comprehensive rust prevention is of great significance to optimizing the comprehensive physical properties of iron-based alloy soft magnetic composite materials. Summary of the invention
[0003] Therefore, the technical problem to be solved by the present invention is to overcome the defects of poor rust prevention effect by immersing in anti-rust oil, high cost and large pollution by spraying paint, and the defects of increasing the size of the product and easy falling off, and the inability to take into account both rust prevention performance and magnetic properties by silane coupling agent treatment, and to provide a rust-proof soft magnetic composite material and its preparation method and application.
[0004] To this end, the present invention provides the following technical solutions: A first aspect of the present invention provides a method for preparing a rust-proof soft magnetic composite material, wherein the preparation method comprises the following steps: S1, using a coating liquid to coat the iron-based powder for the first time, adding silicone resin and solvent to solidify, crushing to obtain coated iron-based powder, and then molding and annealing; S2, performing a second coating on the annealed product using a coating liquid, and obtaining a rust-proof soft magnetic composite material after drying and baking; Wherein, the coating solution includes nano oxide and silane coupling agent.
[0005] According to the present invention, the specific preparation method of the coating liquid comprises the following steps: a nano-oxide, a first solvent, a wetting agent, a dispersant and a stabilizer are first mixed to obtain a modified nano-oxide rust preventive liquid; a silane coupling agent, a second solvent, a weak acid reagent and a diluent are second mixed to obtain a mixed liquid, and the modified nano-oxide rust preventive liquid is added to the mixed liquid for a third mixing to obtain a coating liquid.
[0006] According to the present invention, before the first coating, the method further includes the steps of pre-coating and pre-annealing the iron-based powder with a coating liquid to obtain a pre-coated iron-based powder.
[0007] In the present invention, the coating liquid used for the first coating of the pre-coated iron-based powder is not the coating liquid used in the pre-coating process, but a fresh coating liquid.
[0008] According to the present invention, the nano-oxide includes gas-phase nano-silicon dioxide and / or gas-phase nano-aluminum oxide.
[0009] According to the present invention, based on the mass of the first solvent, the mass of the nano-oxide is 5-7wt%, the mass of the wetting agent is 0.2-0.5wt%, the mass of the dispersant is 0.2-0.8wt%, and the mass of the stabilizer is 0.4-1wt%.
[0010] According to the present invention, the nano-oxide is a mixture with different particle sizes, and the average particle size of the nano-oxide is 20-100 nm.
[0011] According to the present invention, the first solvent includes an alcohol solvent.
[0012] In the present invention, the alcohol solvent includes at least one of ethanol and propanol.
[0013] According to the present invention, the wetting agent includes a nonionic organic wetting agent. Further, the wetting agent includes at least one of alkyl alcohol polyoxyethylene ether (such as Triton X-100) and alkylphenol polyoxyethylene ether (such as OP-10, YHC0019S).
[0014] According to the present invention, the dispersant includes a non-ionic organic dispersant. Further, the dispersant includes at least one of polyvinyl pyrrolidone (PVP) and polyvinyl alcohol (PVA).
[0015] According to the present invention, the stabilizer includes at least one of silane compounds; further, the silane compound includes γ-aminopropyltriethoxysilane.
[0016] According to the present invention, the mass ratio of the silane coupling agent, the second solvent, the weak acid reagent and the diluent is 1:(90-140):(0.05-0.8):(10-20), and can be optionally 1:(100-120):(0.1-0.3):(10-15).
[0017] According to the present invention, the silane coupling agent includes at least one of an aminosilane coupling agent and an acrylic silane coupling agent.
[0018] In the present invention, the aminosilane coupling agent may specifically be KH550 or KH570.
[0019] According to the present invention, the second solvent comprises an alcohol solvent.
[0020] In the present invention, the alcohol solvent includes at least one of ethanol and propanol.
[0021] According to the present invention, the weak acid reagent comprises an inorganic acid, optionally phosphoric acid.
[0022] According to the present invention, the diluent comprises water.
[0023] According to the present invention, the temperature of the first mixing is 20-30° C. and the time is 10-15 min.
[0024] According to the present invention, the temperature of the second mixing is 30-40° C. and the time is 30-40 min.
[0025] According to the present invention, the temperature of the third mixing is 70-90° C. and the time is 30-40 minutes.
[0026] According to the present invention, in the pre-coating, the mass ratio of the iron-based powder to the silane coupling agent in the coating liquid is 100:0.3-0.8.
[0027] According to the present invention, the iron-based powder includes iron powder and / or magnetic iron-based alloy powder. Further, the magnetic iron-based alloy powder includes at least one of iron powder, Sendust aluminum alloy, Iron-nickel alloy and Iron-silicon alloy.
[0028] According to the present invention, the iron-based powder has different particle sizes, and the average particle size of the iron-based powder is 10-60 μm.
[0029] According to the present invention, the pre-coating temperature is 50-80°C and the time is 50-100 min; alternatively, the pre-coating temperature is 60-70°C and the time is 60-90 min.
[0030] According to the present invention, the pre-annealing temperature is 750-850° C. and the time is 60-90 min.
[0031] In the present invention, the product obtained by pre-annealing after natural cooling is also crushed and screened, and the specific average particle size is selected according to actual needs.
[0032] According to the present invention, in the first coating, the mass ratio of the iron-based powder to the silane coupling agent in the coating liquid is 100:0.3-0.8.
[0033] According to the present invention, the temperature of the first coating is 50-80°C, and the time is 50-100 min; optionally, the temperature of the first coating is 60-70°C, and the time is 60-90 min.
[0034] According to the present invention, the silicone resin includes an organic silicone resin; optionally, the organic silicone resin includes at least one of methyl silicone resin, ethyl silicone resin, and polydimethylsiloxane.
[0035] According to the present invention, the solvent includes a ketone solvent and / or an ester solvent. Optionally, the solvent includes at least one of acetone and ethyl acetate.
[0036] According to the present invention, based on the mass of the iron-based powder, the mass of the silicone resin is 0.8-1.2 wt %, and the mass of the solvent is 2-3 wt %.
[0037] According to the present invention, the curing temperature is 60-80° C. and the curing time is 30-60 min.
[0038] In the present invention, curing can increase the overall bonding strength of the system, enhance formability, and facilitate subsequent operations. The coated iron-based powder obtained after curing and cooling is sieved, and the specific average particle size is selected according to actual needs.
[0039] According to the present invention, the molding temperature is 20-30° C., the pressure is 800-2000 MPa, and the time is 10-20 s.
[0040] According to the present invention, a release agent is also added during the molding.
[0041] According to the present invention, the mass of the release agent is 0.3-0.4 wt % based on the mass of the iron-based powder.
[0042] According to the present invention, the release agent is a stearate, including zinc stearate and / or aluminum stearate.
[0043] According to the present invention, the annealing temperature is 650-750° C. and the annealing time is 60-90 min.
[0044] In the present invention, the annealing can remove the internal stress generated during the forming and pressing process. The gas atmosphere of the annealing is a protective gas, and typically, but not limitingly, the gas atmosphere is nitrogen.
[0045] According to the present invention, in the second coating, the mass ratio of the annealed product to the silane coupling agent in the coating liquid is 100:0.3-0.8.
[0046] According to the present invention, the temperature of the second coating is 70-90° C. and the time is 60-90 min.
[0047] According to the present invention, the drying temperature is 60-80° C. and the drying time is 60-120 min.
[0048] According to the present invention, the baking temperature is 180-240° C. and the baking time is 60-90 minutes.
[0049] The second aspect of the present invention protects a rust-proof soft magnetic composite material prepared by the aforementioned preparation method.
[0050] The third aspect of the present invention protects the use of the aforementioned rust-proof soft magnetic composite material in an inductor, a transformer, a filter, a motor or a sensor.
[0051] The technical solution of the present invention has the following advantages: 1. A method for preparing a rust-proof soft magnetic composite material, wherein the preparation method comprises the following steps: S1, using a coating liquid to perform a first coating on an iron-based powder, adding silicone resin and a solvent to solidify, crushing, obtaining a coated iron-based powder, and then molding and annealing; S2, using a coating liquid to perform a second coating on the annealed product, drying, and baking to obtain a rust-proof soft magnetic composite material; wherein the coating liquid comprises nano-oxides and silane coupling agents; the present invention does not adopt the method of dipping in rust-proof oil or the method of spraying paint, thereby avoiding the disadvantages of these two methods; the present invention achieves a multi-step coating synergistic effect through the first coating and the second coating , even if the soft magnetic composite material is worn or cracked during use, due to the existence of the outer coating layer of the iron-based powder, the overall rust resistance is still good, ensuring that the soft magnetic composite material can be used for a long time; the first coating specifically uses a silane coupling agent to modify the surface of the iron-based powder to generate a Si-O bond, and the remaining O end of the Si-O bond is connected to the element in the nano-oxide with excellent hydrophobic and insulating properties to form a coating layer, so that the rust-proof soft magnetic composite material can take into account both rust resistance and magnetic properties; in addition, the second coating effectively repairs the coating layer of the intermediate product damaged by molding and pressing, prevents high loss, and enhances the rust-proof effect.
[0052] 2. In the present invention, a specific coating liquid preparation method comprises the following steps: firstly, nano-oxide, a first solvent, a wetting agent, a dispersant and a stabilizer are mixed for a first time to obtain a modified nano-oxide rust preventive liquid, wherein the wetting agent, the dispersant and the stabilizer act synergistically to make the rust preventive liquid uniform and stable; secondly, a silane coupling agent, a second solvent, a weak acid reagent and a diluent are mixed for a second time to obtain a mixed liquid, and the modified nano-oxide rust preventive liquid is added to the mixed liquid for a third time to obtain a coating liquid; the weak acid in the coating liquid is used to catalyze the hydrolysis of the silane coupling agent, because there are multiple components in the coating liquid, and the weak acid has low acidity and will not react with the metal to passivate the metal surface, so the deterioration of the magnetic properties caused by strong acid pickling can be avoided; and the stepwise addition makes the mixing more sufficient, and the coating liquid finally formed is a relatively stable colloid, in which the nano-oxide is evenly distributed, which helps the hydrolysis product of the silane coupling agent and the nano-oxide to be evenly coated on the surface of the iron-based powder during coating, thereby ensuring the uniformity and stability of the coating layer; In the present invention, a pre-coating and pre-annealing process is first performed, and then the first coating is performed, which can make the coating more uniform. The pre-coating and the first coating work synergistically to form a solid coating layer on the surface of the iron-based powder, thereby enhancing the strength of the overall coating layer, and can effectively avoid the situation in which the coating layer falls off due to high pressure applied in the subsequent molding process.
[0053] 3. In the present invention, the specific types and amounts of the nano-oxide, the first solvent, and the additive can further improve the uniformity and stability of the dispersion of the nano-oxide in the rust-proof liquid, making the formed coating layer more uniform and stable.
[0054] 4. In the present invention, the specific types and amounts of the silane coupling agent, the second solvent, the acid agent and the diluent can further increase the amount of silanol produced by the hydrolysis of the silane coupling agent, so that the surface modification of the iron-based powder is more sufficient, and the uniformity and adhesion of the subsequent film formation are ensured.
[0055] 5. The present invention further limits the pre-coating conditions, which can further improve the uniformity and film-forming strength of the iron-based powder surface coating layer, ensure the insulation between the powders, and improve the resistivity of the prepared soft magnetic composite material, so that the final soft magnetic composite material has lower loss.
[0056] 6. The present invention further defines the pre-annealing conditions, which can further improve the bonding force of the Si-O-bonds from the elements in the nano-oxide formed on the surface of the iron-based powder after sintering, thereby ensuring the strength and insulation of the coating layer.
[0057] 7. The present invention further limits the coating conditions, which can further improve the uniformity and film-forming strength of the coating layer on the surface of the iron-based powder, further improve the insulation between the powders, and thus further reduce the loss characteristics of the obtained soft magnetic composite material.
[0058] 8. The present invention further limits the second coating condition, which can further improve the uniformity and film strength of the soft magnetic composite material coating layer, increase the overall insulation, surface hydrophobicity and air isolation ability of the soft magnetic composite material, thereby further reducing losses and improving the rust resistance of the soft magnetic composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0060] Figure 1 is a SEM image of the uncoated iron-based powder in Example 1; Figure 2 is a SEM image of the coated iron-based powder in Example 1; Figure 3 This is a picture of the rust-proof soft magnetic composite material provided in Example 1 after being subjected to a double 85 test for 960 hours; Figure 4 This is a picture of the rust-proof soft magnetic composite material provided in Example 1 after double 85 test for 24 hours; Figure 5 This is a picture of the rust-proof soft magnetic composite material provided in Example 2 after being subjected to a double 85 test for 960 hours; Figure 6 This is a picture of the rust-proof soft magnetic composite material provided in Example 2 after the double 85 test for 12 hours. DETAILED DESCRIPTION
[0061] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0062] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0063] Fumed nano-silica: from Hubei Huifu Materials Co., Ltd., brand HB-139; Fumed nano-alumina: from Hubei Huifu Materials Co., Ltd., brand ALUNA-100; Iron-silicon-aluminum alloy powder: from Henan Zhongzuan New Materials Co., Ltd., the composition includes 85wt% iron, 9wt% silicon and 6wt% aluminum; Iron-silicon alloy powder: from Henan Zhongzuan New Materials Co., Ltd., the composition includes 95.5wt% iron and 4.5wt% silicon; Wetting agent YHC3031S: Foshan Youhua New Material Technology Co., Ltd. Dispersant YHC0019S: Foshan Youhua New Material Technology Co., Ltd.; Stabilizer YHC0090S: Foshan Youhua New Material Technology Co., Ltd.; The concentration of phosphoric acid is 85wt%; Water is deionized water; Polydimethylsiloxane (Shanghai Dingfen Chemical Technology Co., Ltd., weight average molecular weight 9000-14000 g / mol); Forming is done using a servo press.
[0064] Example 1 This embodiment provides a method for preparing a rust-proof soft magnetic composite material, and the specific method is: S1, 5g of fumed nano-silica with an average particle size of 60nm, 100g of ethanol, 0.2g of wetting agent YHC3031S, 0.2g of dispersant YHC0019S and 0.5g of stabilizer YHC0090S were mixed at 25°C and allowed to stand for 10min to obtain a modified fumed nano-silica rust preventive liquid; 4g of silane coupling agent KH550, 400g of ethanol, 1g of phosphoric acid and 50g of deionized water were mixed at 25°C and allowed to stand for 30min to obtain a mixed solution, all the modified fumed nano-silica rust preventive liquids were added to the mixed solution, and the mixture was heated in a water bath at 80°C for 30min, and a third mixing was performed to obtain a coating solution; S2, using the coating liquid in S1 to pre-coat 1 kg of Sendust aluminum alloy powder with an average particle size of 35 μm, wherein the mass ratio of the Sendust aluminum alloy powder to the silane coupling agent KH550 in the coating liquid is 100:0.4, the pre-coating temperature is 60° C., and the time is 60 min; and pre-annealing is performed at a temperature of 780° C. and a time is 60 min, and the powder is naturally cooled and sieved to obtain the pre-coated Sendust aluminum alloy powder; S3, using the coating liquid in S1 to perform the first coating on the pre-coated Sendust aluminum alloy powder, wherein the mass ratio of the Sendust aluminum alloy powder to the silane coupling agent KH550 in the coating liquid is 100:0.4, the temperature of the first coating is 60°C, the time is 60min, 8g of polydimethylsiloxane and 20g of acetone are added for curing, and the powder is baked at 60°C for 60min, cooled naturally, and crushed and sieved to obtain the coated Sendust aluminum alloy powder. The Sendust aluminum alloy powder is not coated as shown in the picture Figure 1 As shown, the picture of coated iron silicon aluminum alloy powder is as follows Figure 2 As shown, in Figure 2 It can be seen that the surface of the sendust powder is evenly coated and the coating effect is good; 4g of zinc stearate is added and mixed, and the molding is carried out. The molding temperature is 25°C, the pressure is 1800MPa, the pressure is maintained for 10s, and annealing is carried out in a nitrogen environment. The annealing temperature is 700°C and the time is 60min. S4, using the coating liquid in S1 to perform a second coating on the annealed product, wherein the mass ratio of the annealed product to the silane coupling agent KH550 in the coating liquid is 100:0.5, the temperature of the second coating is 80°C, the time is 60min, and it is dried in an oven at 60°C for 120min, and then baked at 220°C for 60min to obtain a rust-proof soft magnetic composite material; the situation of the double 85 test for 960h in Example 1 is as follows Figure 3 As shown, from Figure 3 It can be seen that the surface of the rust-proof soft magnetic composite material (ring material) is smooth and has no rust spots.
[0065] Example 2 This embodiment provides a method for preparing a rust-proof soft magnetic composite material, and the specific method is: S1, 5g of fumed nano-silica with an average particle size of 75nm, 100g of ethanol, 0.2g of wetting agent YHC3031S, 0.2g of dispersant YHC0019S and 0.5g of stabilizer YHC0090S were mixed at 25°C and allowed to stand for 10min to obtain a modified fumed nano-silica rust preventive liquid; 6g of silane coupling agent KH550, 700g of ethanol, 2g of phosphoric acid and 80g of deionized water were mixed at 25°C and allowed to stand for 30min to obtain a mixed solution, all the modified fumed nano-silica rust preventive liquids were added to the mixed solution, and the mixture was heated in a water bath at 80°C for 30min, and a third mixing was performed to obtain a coating solution; S2, using the coating liquid in S1 to pre-coat 1 kg of iron-silicon alloy powder with an average particle size of 30 μm, wherein the mass ratio of the iron-silicon alloy powder to the silane coupling agent KH550 in the coating liquid is 100:0.4, the pre-coating temperature is 60° C., and the time is 60 min; and pre-annealing is performed at a temperature of 760° C. and a time is 60 min, and the powder is naturally cooled and sieved to obtain the pre-coated iron-silicon alloy powder; S3, using the coating liquid in S1 to perform a first coating on the pre-coated iron-silicon alloy powder, wherein the mass ratio of the iron-silicon alloy powder to the silane coupling agent KH550 in the coating liquid is 100:0.5, the temperature of the first coating is 60°C, the time is 60 min, 12g of polydimethylsiloxane and 30g of acetone are added for curing, baked at 60°C for 60 min, naturally cooled, crushed and sieved to obtain coated iron-silicon alloy powder, 4g of zinc stearate is added and mixed, and molding is performed, the molding temperature is 25°C, the pressure is 1000MPa, the pressure is maintained for 10s, and annealing is performed in a nitrogen environment at a temperature of 750°C for 60 min; S4, using the coating liquid in S1 to perform a second coating on the annealed product, wherein the mass ratio of the annealed product to the silane coupling agent KH550 in the coating liquid is 100:0.5, the temperature of the second coating is 80°C, the time is 60min, and it is dried in an oven at 60°C for 120min, and then baked at 240°C for 60min to obtain a rust-proof soft magnetic composite material; the situation of the double 85 test for 960h in Example 2 is as follows Figure 5 As shown, Example 2 and Example 1 are pressed using different molds, so the configuration of the rust-proof soft magnetic composite material is different. Figure 5 It can be seen that the surface of the rust-proof soft magnetic composite material is smooth and has no rust spots.
[0066] Example 3 This embodiment provides a method for preparing a rust-proof soft magnetic composite material, and the specific method is: The method of Example 1 is followed, except that “5 g of fumed nano-silica with an average particle size of 60 nm, 100 g of ethanol, 0.2 g of wetting agent YHC3031S, 0.2 g of dispersant YHC0019S and 0.5 g of stabilizer YHC0090S” is changed to “5 g of fumed nano-silica with an average particle size of 60 nm, 100 g of ethanol, 0.4 g of wetting agent Triton X-100, 0.3 g of dispersant polyvinyl pyrrolidone and 0.4 g of stabilizer γ-aminopropyltriethoxysilane”.
[0067] Example 4 This embodiment provides a method for preparing a rust-proof soft magnetic composite material, and the specific method is: The method of Example 1 is followed, except that “6 g of silane coupling agent KH550, 700 g of ethanol, 2 g of phosphoric acid and 80 g of deionized water” is changed to “5 g of silane coupling agent KH570, 700 g of ethanol, 4 g of phosphoric acid and 80 g of deionized water”.
[0068] Example 5 This embodiment provides a method for preparing a rust-proof soft magnetic composite material, and the specific method is: The method of Example 1 is followed, except that "the pre-coating temperature is 60° C. and the time is 60 min" is changed to "the pre-coating temperature is 80° C. and the time is 90 min".
[0069] Example 6 This embodiment provides a method for preparing a rust-proof soft magnetic composite material, and the specific method is: The method of Example 1 is the same, except that "the pre-annealing temperature is 780° C. and the time is 60 min" is changed to "the pre-annealing temperature is 850° C. and the time is 90 min".
[0070] Example 7 This embodiment provides a method for preparing a rust-proof soft magnetic composite material, and the specific method is: The method of Example 1 is followed, except that "the temperature of the first coating is 60° C., and the time is 60 min" is changed to "the temperature of the first coating is 80° C., and the time is 90 min".
[0071] Example 8 This embodiment provides a method for preparing a rust-proof soft magnetic composite material, and the specific method is: The method of Example 1 is followed, except that "the temperature of the second coating is 80° C., and the time is 60 min" is changed to "the temperature of the second coating is 90° C., and the time is 90 min".
[0072] Example 9 This embodiment provides a method for preparing a rust-proof soft magnetic composite material, and the specific method is: The method of Example 1 is the same, except that "the average particle size of 60nm gas-phase nano-silicon dioxide" is changed to "the average particle size of 60nm gas-phase nano-alumina".
[0073] Example 10 This embodiment provides a method for preparing a rust-proof soft magnetic composite material, and the specific method is: The method of Example 1 is the same as that of Example 1, except that "the average particle size of the sendust alloy powder is 35 μm" is changed to "the average particle size of the iron powder is 35 μm".
[0074] Embodiment 11 This embodiment provides a method for preparing a rust-proof soft magnetic composite material, and the specific method is: S1, 5g of fumed nano-silica with an average particle size of 60nm, 100g of ethanol, 0.2g of wetting agent YHC3031S, 0.2g of dispersant YHC0019S and 0.5g of stabilizer YHC0090S were mixed at 25°C and allowed to stand for 10min to obtain a modified fumed nano-silica rust preventive liquid; 4g of silane coupling agent KH550, 400g of ethanol, 1g of phosphoric acid and 50g of deionized water were mixed at 25°C and allowed to stand for 30min to obtain a mixed solution, all the modified fumed nano-silica rust preventive liquids were added to the mixed solution, and the mixture was heated in a water bath at 80°C for 30min, and a third mixing was performed to obtain a coating solution; S2, using the coating liquid in S1 to perform a first coating on the Sendust aluminum alloy powder, wherein the mass ratio of the Sendust aluminum alloy powder to the silane coupling agent KH550 in the coating liquid is 100:0.4, the temperature of the first coating is 60°C, the time is 60 min, 8g of polydimethylsiloxane and 20g of acetone are added for curing, baked at 60°C for 60 min, naturally cooled, crushed and sieved to obtain coated Sendust aluminum alloy powder, 4g of zinc stearate is added and mixed, and molding is performed, the molding temperature is 25°C, the pressure is 1800MPa, the pressure is maintained for 10s, and annealing is performed in a nitrogen environment at a temperature of 700°C for 60 min; S3, using the coating liquid in S1 to perform a second coating on the annealed product, wherein the mass ratio of the annealed product to the silane coupling agent KH550 in the coating liquid is 100:0.5, the temperature of the second coating is 80°C, the time is 60 min, drying in a 60°C oven for 120 min, and then baking at 220°C for 60 min to obtain a rust-proof soft magnetic composite material.
[0075] Comparative Example 1 This comparative example provides a method for preparing a soft magnetic composite material, and the specific method is: 1 kg of Sendust aluminum alloy powder with an average particle size of 35 μm, 8 g of polydimethylsiloxane, and 20 g of acetone were mixed and solidified, baked at 60° C. for 60 min, naturally cooled, crushed and sieved to obtain coated Sendust aluminum alloy powder, 4 g of zinc stearate was added and mixed, and molded at a molding temperature of 25° C. and a pressure of 1800 MPa. The pressure was maintained for 10 s, and annealed in a nitrogen environment at a temperature of 700° C. for 60 min. The results of the double 85 test for 24 h in Comparative Example 1 are as follows: Figure 4 As shown, from Figure 4 It can be seen that there are rust spots on the rust-proof soft magnetic composite material.
[0076] Comparative Example 2 This comparative example provides a method for preparing a soft magnetic composite material, and the specific method is: 1kg of iron-silicon alloy powder with an average particle size of 35μm, 12g of polydimethylsiloxane, and 30g of acetone were solidified, baked at 60°C for 60min, naturally cooled, crushed and sieved to obtain coated iron-silicon alloy powder, 4g of zinc stearate was added and mixed, and molded at a molding temperature of 25°C and a pressure of 1000MPa. The pressure was maintained for 10s and annealed in a nitrogen environment at a temperature of 750°C for 1h. The case of double 85 test for 12h in comparative example 2 is as follows Figure 6 As shown, from Figure 6 It can be seen that there are a lot of rust spots on the rust-proof soft magnetic composite material.
[0077] Comparative Example 3 This comparative example provides a method for preparing a rust-proof soft magnetic composite material, and the specific method is: The method of Example 1 is the same, except that the "fumed nano-silica with an average particle size of 60 nm" is changed to "ordinary silicon dioxide with an average particle size of 15 μm".
[0078] Comparative Example 4 This comparative example provides a method for preparing a rust-proof soft magnetic composite material, and the specific method is: S1, 5g of fumed nano-silica with an average particle size of 60nm, 100g of ethanol, 0.2g of wetting agent YHC3031S, 0.2g of dispersant YHC0019S and 0.5g of stabilizer YHC0090S were mixed at 25°C and allowed to stand for 10min to obtain a modified fumed nano-silica rust preventive liquid; 4g of silane coupling agent KH550, 400g of ethanol, 1g of phosphoric acid and 50g of deionized water were mixed at 25°C and allowed to stand for 30min to obtain a mixed solution, all the modified fumed nano-silica rust preventive liquids were added to the mixed solution, and the mixture was heated in a water bath at 80°C for 30min, and a third mixing was performed to obtain a coating solution; S2, using the coating liquid in S1 to pre-coat 1 kg of Sendust aluminum alloy powder with an average particle size of 35 μm, wherein the mass ratio of the Sendust aluminum alloy powder to the silane coupling agent KH550 in the coating liquid is 100:0.4, the pre-coating temperature is 60° C., and the time is 60 min; and pre-annealing is performed at a temperature of 780° C. and a time is 60 min, and the powder is naturally cooled, crushed and sieved to obtain the pre-coated Sendust aluminum alloy powder; S3, using the coating liquid in S1 to coat the pre-coated Sendust aluminum alloy powder, wherein the mass ratio of the Sendust aluminum alloy powder to the silane coupling agent KH550 in the coating liquid is 100:0.4, the coating temperature is 60°C, the time is 60 min, 8g of polydimethylsiloxane and 20g of acetone are added for curing, baked at 60°C for 60 min, naturally cooled, crushed and sieved to obtain coated Sendust aluminum alloy powder, 4g of zinc stearate is added and mixed, and molding is performed at a molding temperature of 25°C and a pressure of 1800MPa. The pressure is maintained for 10s, and annealing is performed in a nitrogen environment at a temperature of 700°C for 60 min to obtain a rust-proof soft magnetic composite material.
[0079] Test Case According to the standard SJ20966-2006, the properties of the prepared soft magnetic composite materials were tested using an IWATSUB-H analyzer (SY-8219), with an applied magnetic field frequency of 50 kHz and a magnetic field intensity of 100 mT; The soft magnetic composite material was subjected to a double 85 (85°C, relative humidity 85% RH) experiment, observed every 12 hours, and the test duration was 960 hours. If rust spots appeared within 960 hours, the time when the rust spots appeared was recorded; if no rust spots appeared after the test time reached 960 hours, the result was recorded as "none" after observation to evaluate the anti-rust performance; The specific results are shown in Table 1.
[0080] Table 1 Loss and rust spots of soft magnetic composite materials tested
[0081] The raw material in Example 1 is an iron-silicon alloy powder, the raw material in Example 2 is an iron-silicon alloy powder, and the raw material in Example 10 is iron powder. The embodiments are different iron-based powders. The loss of the existing iron-silicon-aluminum soft magnetic composite material is 140mW / cm 3 The loss of iron-silicon soft magnetic composite material is about 400mW / cm 3 The loss of pure iron soft magnetic composite material is about 500W / cm 3 The soft magnetic composite material prepared by the present invention has lower loss and better magnetic properties than the existing soft magnetic composite materials; moreover, the soft magnetic composite material prepared by the present invention will not have rust spots or it will take a longer time for rust spots to appear, and can take into account both anti-rust performance and magnetic properties.
[0082] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.
Claims
1. A method for preparing a rust-proof soft magnetic composite material, characterized in that: The preparation method comprises the following steps: S1, using a coating liquid to coat the iron-based powder for the first time, adding silicone resin and solvent to solidify, crushing to obtain coated iron-based powder, and then molding and annealing; S2, performing a second coating on the annealed product using a coating liquid, and obtaining a rust-proof soft magnetic composite material after drying and baking; Wherein, the coating solution includes nano oxide and silane coupling agent.
2. The preparation method according to claim 1, characterized in that: The specific preparation method of the coating liquid comprises the following steps: first mixing nano oxide, a first solvent, a wetting agent, a dispersant and a stabilizer to obtain a modified nano oxide rust preventive liquid; second mixing a silane coupling agent, a second solvent, a weak acid reagent and a diluent to obtain a mixed liquid, and adding the modified nano oxide rust preventive liquid to the mixed liquid for third mixing to obtain a coating liquid; And / or, before the first coating, the method further includes the steps of pre-coating and pre-annealing the iron-based powder with a coating liquid to obtain a pre-coated iron-based powder.
3. The preparation method according to claim 2, characterized in that: The nano oxide includes gas phase nano silicon dioxide and / or gas phase nano aluminum oxide; And / or, based on the mass of the first solvent, the mass of the nano-oxide is 5-7wt%, the mass of the wetting agent is 0.2-0.5wt%, the mass of the dispersant is 0.2-0.8wt%, and the mass of the stabilizer is 0.4-1wt%; And / or, the average particle size of the nano-oxide is 20-100 nm; and / or, the first solvent comprises an alcohol solvent; and / or, the wetting agent comprises a nonionic organic wetting agent; and / or, the dispersant comprises a nonionic organic dispersant; And / or, the stabilizer includes at least one of silane compounds; And / or, the mass ratio of the silane coupling agent, the second solvent, the weak acid reagent and the diluent is 1:(90-140):(0.05-0.8):(10-20); And / or, the silane coupling agent includes at least one of an aminosilane coupling agent and an acrylic silane coupling agent; and / or, the second solvent comprises an alcohol solvent; and / or, the weak acid reagent comprises an inorganic acid; and / or, the diluent comprises water; And / or, the first mixing temperature is 20-30°C and the time is 10-15min; And / or, the temperature of the second mixing is 30-40°C and the time is 30-40min; And / or, the third mixing is carried out at a temperature of 70-90° C. and for a time of 30-40 min.
4. The preparation method according to claim 3, characterized in that: The wetting agent includes at least one of alkyl alcohol polyoxyethylene ether and alkylphenol polyoxyethylene ether; And / or, the dispersant includes at least one of polyvinyl pyrrolidone and polyvinyl alcohol; And / or, the silane compound includes γ-aminopropyltriethoxysilane; And / or, the mass ratio of the silane coupling agent, the second solvent, the weak acid reagent and the diluent is 1:(100-120):(0.1-0.3):(10-15); And / or, the weak acid reagent includes phosphoric acid.
5. The preparation method according to claim 2, characterized in that: In the pre-coating, the mass ratio of the iron-based powder to the silane coupling agent in the coating liquid is 100:0.3-0.8; And / or, the iron-based powder includes iron powder and / or magnetic iron-based alloy powder; And / or, the average particle size of the iron-based powder is 10-60 μm; And / or, the pre-coating temperature is 50-80°C and the time is 50-100min; And / or, the pre-annealing temperature is 750-850°C and the time is 60-90min; And / or, in the first coating, the mass ratio of the iron-based powder to the silane coupling agent in the coating liquid is 100:0.3-0.8; And / or, the temperature of the first coating is 50-80°C and the time is 50-100 min; and / or, the silicone resin comprises an organic silicone resin; and / or, in the curing step, the solvent comprises a ketone solvent and / or an ester solvent; And / or, in the curing step, based on the mass of the iron-based powder, the mass of the silicone resin is 0.8-1.2wt%, and the mass of the solvent is 2-3wt%; And / or, the curing temperature is 60-80°C and the curing time is 30-60min; And / or, the molding temperature is 20-30°C, the pressure is 800-2000MPa, and the time is 10-20s; And / or, a release agent is also added during the molding; And / or, the annealing temperature is 650-750° C. and the annealing time is 60-90 min.
6. The preparation method according to claim 5, characterized in that: The magnetic iron-based alloy powder includes at least one of iron powder, iron-silicon-aluminum alloy, iron-nickel alloy and iron-silicon alloy; And / or, the pre-coating temperature is 60-70° C. and the pre-coating time is 60-90 min.
7. The preparation method according to claim 5, characterized in that: The first coating temperature is 60-70°C and the time is 60-90min; And / or, the organic silicone resin includes at least one of methyl silicone resin, ethyl silicone resin, and polydimethylsiloxane; And / or, in the curing step, the solvent includes at least one of acetone and ethyl acetate; and / or, in the curing step, the mass of the release agent is 0.3-0.4wt% based on the mass of the iron-based powder; And / or, the release agent comprises stearate.
8. The preparation method according to any one of claims 1 to 7, characterized in that: In the second coating, the mass ratio of the annealed product to the silane coupling agent in the coating solution is 100:0.3-0.8; And / or, the temperature of the second coating is 70-90°C and the time is 60-90min; And / or, the drying temperature is 60-80°C and the drying time is 60-120min; And / or, the baking temperature is 180-240° C. and the baking time is 60-90 min.
9. A rust-proof soft magnetic composite material prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the rust-proof soft magnetic composite material according to claim 9 in an inductor, a transformer, a filter, a motor or a sensor.
Citation Information
Patent Citations
Production methods of inorganic-organic insulation layer soft magnetic composites
CN103240411A
Alloy magnetic powder core and preparation method and application thereof
CN112489918A
Magnetic powder core and preparation method thereof
CN115512955A
Organic-inorganic composite coated iron-based soft magnetic composite material and preparation method thereof
CN116137203A
Soft magnetic material and preparation method thereof
CN116153604A